Conformance checking and performance improvement in scheduled processes: A queueing-network perspective. (December 2016) - Senderovich, Arik; Weidlich, Matthias; Yedidsion, Liron; Gal, Avigdor; Mandelbaum, Avishai; Kadish, Sarah; Bunnell, Craig A.
Abstract: Service processes, for example in transportation, telecommunications or the health sector, are the backbone of today׳s economies. Conceptual models of service processes enable operational analysis that supports, e.g., resource provisioning or delay prediction. In the presence of event logs containing recorded traces of process execution, such operational models can be mined automatically. In this work, we target the analysis of resource-driven, scheduled processes based on event logs. We focus on processes for which there exists a pre-defined assignment of activity instances to resources that execute activities. Specifically, we approach the questions of conformance checking ( how to assess the conformance of the schedule and the actual process execution ) and performance improvement ( how to improve the operational process performance ). The first question is addressed based on a queueing network for both the schedule and the actual process execution. Based on these models, we detect operational deviations and then apply statistical inference and similarity measures to validate the scheduling assumptions, thereby identifying root-causes for these deviations. These results are the starting point for our technique to improve the operational performance. It suggests adaptations of the scheduling policy of the service process to decrease the tardiness (non-punctuality) and lower the flow time. We demonstrate the value of our approach based on a real-world dataset comprising clinical pathways of an outpatient clinic that have been recorded by a real-time location system (RTLS). Our results indicate that the presented technique enables localization of operational bottlenecks along with their root-causes, while our improvement technique yields a decrease in median tardiness and flow time by more than 20%. Abstract : Highlights: We provide a broad extension to the notions of conceptual, operational and continuous conformance checking techniques. We present novel theoretical results in terms of scheduling algorithms for Fork/Join networks that re-sequence arriving cases. We prove that these scheduling algorithms are guaranteed to never perform worse than the baseline approach. We test the new techniques for process improvement on real-world data, and show that the proposed algorithms yield a 20%-40% improvement in median flow time and tardiness.